If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -25 = 5(4q + -10) + -5q Reorder the terms: -25 = 5(-10 + 4q) + -5q -25 = (-10 * 5 + 4q * 5) + -5q -25 = (-50 + 20q) + -5q Combine like terms: 20q + -5q = 15q -25 = -50 + 15q Solving -25 = -50 + 15q Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '-15q' to each side of the equation. -25 + -15q = -50 + 15q + -15q Combine like terms: 15q + -15q = 0 -25 + -15q = -50 + 0 -25 + -15q = -50 Add '25' to each side of the equation. -25 + 25 + -15q = -50 + 25 Combine like terms: -25 + 25 = 0 0 + -15q = -50 + 25 -15q = -50 + 25 Combine like terms: -50 + 25 = -25 -15q = -25 Divide each side by '-15'. q = 1.666666667 Simplifying q = 1.666666667
| Y=0.5x+6 | | -2x+4(1-3x)=2x-4(6x+5) | | 1-4n+3=4n-7n-2 | | 9(5b+4)= | | -(a+1)=7-a | | y+30=8 | | 0.3(x+100)+1.5=111 | | 36x-90-30x-60-3x-15=16x+24-6x+6-6+8x | | 10.19-3.3q+7.2q=2.8q-11.59 | | 3x+30=X-2 | | 3x+7x=4x-9 | | 4ab+4a= | | -6.5z+2.26=-17.74-7.5z | | -5w-(7z-6w)-2z= | | 12-m-9m=-20-12m | | x+8=1-6x | | -4w-5(-7x+4w)+6x= | | -3(x-5)-(2x+13)=-4(2x+2)+2(x-3)-2x-4x | | x+10=-y+10 | | -4(-3w-3z)-2(-6z-w)= | | 5x-2-3x=17+12x-23 | | 8f+9=21 | | 5n-n=0 | | -2(3h-1)=5(2h-3) | | g+9+7g=-11+9g | | 2a+4=5a-8 | | 26+8m=6-4(1-5m) | | 9-10v=-9v+13 | | 5(y+5)=y+37 | | -3[x+6]+5=-4 | | 4(5-w)=2(2w-3) | | 36=0.9y |